184k views
5 votes
–2(3x – 1) = –6x – 1

User Mike Pala
by
4.6k points

2 Answers

3 votes
get rid of the parenthesis by multiplying
it becomes
-6x+2=-6x-1
then, i would add one to each side
-6x+3=-6x
subtract -6x from each side
3=-12x
then divide each side by -12. this would make x equal to -3/12 or -1/4
User Yeah
by
5.5k points
3 votes

Answer:

Move all terms to the left side and set equal to zero. Then set each factor equal to zero.

Exact Form:x=4+√22/6,4−√22/6

Explanation:

User Glenn Moss
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.